Exosomes in immunoregulation of chronic lung diseases. Issue 4 (8th December 2016) - Hough, K. P.; Chanda, D.; Duncan, S. R.; Thannickal, V. J.; Deshane, J. S.
Abstract: Exosomes are nano‐sized, membrane‐bound vesicles released from cells that transport cargo including DNA, RNA, and proteins, between cells as a form of intercellular communication. In addition to their role in intercellular communication, exosomes are beginning to be appreciated as agents of immunoregulation that can modulate antigen presentation, immune activation, suppression, and surveillance. This article summarizes how these multifaceted functions of exosomes may promote development and/or progression of chronic inflammatory lung diseases including asthma, chronic obstructive pulmonary disease, and pulmonary fibrosis. The potential of exosomes as a novel therapeutic is also discussed.